(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate physical-mechanical properties, degree of conversion, and chemical stability of a nanohybrid composite containing diatomite as filler. Degree of conversion (DC%) of diatomite-containing composite (Zirconfill®) was performed using FTIR immediately, and 1-, and 7-days post-curing. SEM was conducted to evaluate the surface of the resin after curing and measure particles size. Also, elemental characterization was performed to verify the major components of the composite through EDS. Mechanical characterization using 3-point bending test was performed prior and after thermo-cycling (10000 cycles) (n=10). Knoop microhardness (KHN) was used to characterize mechanical stability after chemical solutions aggression (water, juice, coffee, coke) up to 28 days (n=10/solution). After data normality evaluation using Shapiro-Wilk, One-way ANOVA and Tukey post hoc were conducted to verify differences between groups for DC% and mechanical properties. Split-plot ANOVA was used to compare groups for microhardness characterization (α=0.05). Immediate DC was 60% and significantly increased up to 80% at 7 days (p<0.05). Flexural strength of the diatomite-containing composite was 136.2 (23.7) MPa and significantly decreased to 75.1 (10.2) as a result of thermo-cycling. The flexural modulus was not significantly affected by the thermo-cycling (p>0.05). All the dietary solutions affected the KHN of the composite up to 21 days. For 28 days, the KHN evidenced and stabilization regarding all the solutions. Diatomite-containing composites present good degree of conversion and relevant mechanical properties and demonstrate time-dependent stability against chemical degradation.